Indirect adjusted comparison of 6-month clinical outcomes between esketamine nasal spray and other real-world polypharmacy treatment strategies for treatment resistant depression: results from the ICEBERG study - Oliveira-Maia, Albino J.; Rive, Benoit; Morrens, Joachim; Godinov, Yordan; Cabrieto, Jedelyn; Perualila, Nolen; Mulhern-Haughey, Siobhán (Frontiers in Psychiatry, 2023)
The efficacy of esketamine nasal spray (NS) as a rapid-acting agent for treatment resistant depression (TRD) was demonstrated in comparisons with placebo, when both were given in addition to a newly initiated selective serotonin reuptake inhibitor (SSRI)/serotonin norepinephrine reuptake inhibitor (SNRI). How esketamine NS compares with commonly used real-world (RW) polypharmacy treatment strategies is not known.ICEBERG was an adjusted indirect treatment comparison that analysed data from SUSTAIN-2 (NCT02497287; clinicaltrials.gov), a long-term, open-label study of esketamine NS plus SSRI/SNRI, and the European Observational TRD Cohort (EOTC; NCT03373253; clinicaltrials.gov), an observational study of routine clinical practice. Data were compared between patients receiving esketamine NS (SUSTAIN-2) and those from the EOTC treated with polypharmacy treatment strategies, either combination or augmentation. Analyses were adjusted for potential confounders, using rescaled average treatment effect among treated estimates. Threshold analyses were conducted to assess potential impact of unmeasured confounders on the robustness of analyses where esketamine NS was found to be significantly superior. Sensitivity analyses were used to understand the impact of analysis method selection and data handling.Esketamine NS treatment resulted in a higher probability of 6-month response (49.7% [95% confidence interval (CI) 45.6-53.9]) and remission (33.6% [95% CI 29.7-37.6]) versus RW polypharmacy (26.8% [95% CI 21.0-32.5] and 19.4%, [95% CI 14.2-24.6], respectively). Relative risk calculations showed esketamine NS was 1.859 (95% CI 1.474-2.345; p<0.0001) times as likely to result in response and 1.735 (1.297-2.322; p=0.0002) times as likely to result in remission versus RW polypharmacy at 6 months. Threshold and extensive sensitivity analyses supported that analyses of esketamine NS superiority were robust.ICEBERG supports esketamine NS being superior to current RW individualised polypharmacy strategies, including augmentation, with benefits extending beyond acute use, to improved chance of 6-month response and remission. While unobserved confounding factors may certainly impact results of an indirect comparison, threshold analysis supported a low likelihood of this affecting the conclusions.